Gaya Pembelajaran dalam Kalangan Pelajar Sarjana Muda Psikologi di Universitas Swasta, Perak - Nor Aroma Abu Bakar; Nor Zorrenee Zorkarphy; Muhammad Fawwaz Farhawiz Mohd Jaafar; Norhanaza Mohd Yunos; Rorlinda Binti Yusof (JUDICIOUS, 2022)
Learning style can be linked to a student's performance. Each student has a unique learning style according to their individual suitability. Lecturer also need to know the learning style preferred by students in order to help increase learning motivation and maximize the learning experience of their students. Accordingly, a quantitative survey design study was conducted on 80 students majoring in psychology at a private university in Perak. The main objective of this study was to identify the types of learning styles most preferred by students and their relationship to data demographics. Questionnaires related to four types of learning styles were distributed to students and analyzed with the help of SPSS software version 24.0. The results of the analysis of this study found that the most preferred learning style by the students of the study sample is the visual type learning style with an average mean score=23.48. The study also found that the demographic factors of gender and race had a positive significance with the learning style preferred by the students (p <0.05). Therefore, several recommendations have been put forward including improving the learning process of students such as improving education policies, maximizing ICT integration, corporatization of universities, diversifying university facilities and evaluation of the quality of teaching and learning sessions.